2020
DOI: 10.1111/gwmr.12407
|View full text |Cite
|
Sign up to set email alerts
|

Field Demonstration of the Horizontal Treatment Well (HRX Well®) for Passive In Situ Remediation

Abstract: This column reviews the general features of PHT3D Version 2, a reactive multicomponent transport model that couples the geochemical modeling software PHREEQC-2 (Parkhurst and Appelo 1999) with three-dimensional groundwater flow and transport simulators MODFLOW-2000 and MT3DMS (Zheng and Wang 1999). The original version of PHT3D was developed by Henning Prommer and Version 2 by Henning Prommer and Vincent Post (Prommer and Post 2010). More detailed information about PHT3D is available at the website http://www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The depth to groundwater is approximately 10 to 15 ft bgs and the total saturated thickness ranges from approximately 5 to 12 ft. The hydraulic conductivity is approximately 0.3 ft per day (ft/d) and the groundwater flux (Darcy velocity) averages 0.11 ft/d (Divine et al 2020). Former activities conducted at the site include electroplating, printed circuit board manufacturing, washing of heavy equipment, missile assembly activities, and photographic processing.…”
Section: Field Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth to groundwater is approximately 10 to 15 ft bgs and the total saturated thickness ranges from approximately 5 to 12 ft. The hydraulic conductivity is approximately 0.3 ft per day (ft/d) and the groundwater flux (Darcy velocity) averages 0.11 ft/d (Divine et al 2020). Former activities conducted at the site include electroplating, printed circuit board manufacturing, washing of heavy equipment, missile assembly activities, and photographic processing.…”
Section: Field Sitesmentioning
confidence: 99%
“…Various remediation activities have been conducted previously at the site, including excavation, in‐situ chemical oxidation, and the installation of a Horizontal Reactive Media Treatment Well (Divine et al 2020); however, ERD is the primary full‐scale groundwater remedy. During the first quarter of 2021 ERD was implemented with the injection of emulsified vegetable oil (EOS Pro™) at more than 200 direct‐push technology (DPT) locations installed at regular intervals along distinct transect lines throughout the plume.…”
Section: Field Sitesmentioning
confidence: 99%
“…The HRX Well concept is particularly well suited for sites where long‐term mass discharge control is a primary performance objective. The concept is described in detail in (Divine et al 2018) and (Divine et al 2020) and has been field demonstrated for chlorinated volatile organic compounds (CVOC) and PFAS treatment using granular zero‐valent iron (ZVI; for CVOCs) and GAC (for PFAS) at three field sites.…”
Section: Technical Maturitymentioning
confidence: 99%